Perception about e-cigarettes in Malaysia : sociodemographic correlates - Cheah, Yong Kang; Teh, Chien Huey; Lim, Kuang Hock; Chee, Cheong Kee (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The prevalence of e-cigarette smoking is increasing. Many people still have a poor understanding of the risks of e-cigarettes. The purpose of this study is to examine sociodemographic factors associated with the perception that e-cigarettes are less dangerous than regular cigarettes. Multivariable logistic regressions are utilised to estimate the effects of sociodemographic factors on the likelihood of having the perception that e-cigarettes are less dangerous than regular cigarettes. A Malaysian nationwide survey that consists of a large sample size (n = 4176) is used for secondary analysis. The survey was conducted in 2011. Younger age, male gender and high educational level are associated with good perception about e-cigarettes. Older individuals are less likely to think that e-cigarettes are less dangerous than regular cigarettes compared with younger individuals (aOR: 0.971; 95% CI: 0.957, 0.985). Males are more likely to have the perception that e-cigarettes are less dangerous than regular cigarettes relative to females (aOR: 2.302; 95% CI: 1.631, 3.249). Having primary (aOR: 0.171; 95% CI: 0.096, 0.304) or secondary (aOR: 0.447; 95% CI: 0.318, 0.629) educational level rather than tertiary educational level is associated with a reduced likelihood of having the perception that e-cigarettes are less dangerous than regular cigarettes. Targeted intervention to the high-risk population plays an important role in determining the perception about e-cigarettes. Nationwide health promotion programmes directed toward changing the perception about e-cigarettes among individuals who think that e-cigarettes are less dangerous than regular cigarettes may be effective in lowering the risk of suffering from the currently unknown long-term negative effect of e-cigarettes.